Team Spirit and Collective Decisions in Social Administration from the Qur’anic Perspective: A Textual Analysis - Hashi, Abdurezak Abdulahi (David Publishing Co., Inc., 2011)
According to the Islamic perspective of social administration, team-spirit and collective decisions are important for social administration. The Qur’an, which is the foundation of Islamic faith, states that solutions to the problems related to social administration and economic development are achievable through team spirit and social cohesion (shura and wuhdah). This paper uses an analytical approach to present the Qur’anic perspective of team-spirit and mutual consultations (shura) in social administration. The Qur’anic terms related to the subject are textually analyzed while opinions of the Muslim exegetes of the Qur’an related to the subject are also unveiled. Keywords: administration, team-spirit, collective decisions, the Qur’anic perspective